Studies in retailing - McClelland, W. Grigor (Oxford : B. Blackwell, 1963)
The first chapter attempts to look at distribution as a whole. The second chapter provides a conspectus, designed for an American audience, of the changes in British retailing through an eventful decade. Chapter 3 focuses on the emergence of the supermarket as the potentially dominant form of outlet in the food trades. Chapters 4 and 5 examine those of interest to sociologists and discuss the supermarket's impact on the distribution of farm produce. Chapters 6 and 7 focus o the determination of prices, and analyse the particular characteristics of modern retailing which are relevant to the development of managers for retail organizations. The final chapter describes, with references, some of the ways in which modern methods of collecting and analyzing data can inform and improve managerial decisions in distributions.
Includes bibliographical references and index.
II 18/01/2019
Loans
Keywords: Grocery trade